Impact of foot progression angle modification on plantar loading in individuals with diabetes mellitus and peripheral neuropathy - Merriwether, Ericka N. (Edorium J Disabil Rehabil, 2016)
AIMS: To determine if participants can reduce foot progression angle (FPA), and if FPA reduction decreases regional plantar stresses and forces in individuals with diabetes. METHODS: DESIGN: Three-group cross-sectional design with repeated measures. SUBJECTS: twenty-eight participants either with diabetes mellitus (DM), diabetes and peripheral neuropathy with (DMPN+NPU) or without a prior history of ulceration (DMPN−NPU) were studied. INTERVENTION: Participants were first instructed to walk over a 3.6 m walkway at their preferred FPA, and then to walk with their foot aligned parallel with the line of gait progression at their self-selected speed. Dynamic plantar kinetics in six masked regions were collected using an EMED-st-P-2 pedobarograph. MAIN MEASURES: Primary outcome measures were FPA, peak plantar pressure (PPP), and force-time integral (FTI). A repeated measures ANOVA was conducted to determine group differences in FPA for both walking conditions. Regional differences in PPPs and FTIs between preferred and corrected walking conditions were analyzed using repeated measures ANCOVA. RESULTS: Participants showed a reduction in FPA magnitude on the ‘Involved’ foot between the preferred and corrected walking conditions (p<0.01). There were no differences in PPPs or FTIs in any mask between walking conditions (p>0.05). CONCLUSION: Results from this investigation offer important evidence that people with diabetes can modify their FPA with a simple intervention of visual and verbal cueing. Future research should examine if gait retraining strategies in regular footwear more effectively offload areas of elevated regional plantar stresses and forces in adults with diabetes mellitus and peripheral neuropathy.